After Emerson - Lysaker, John T. (Book collections on Project MUSE., 2017)
John T. Lysaker works between and weaves together questions and replies in philosophical psychology, Emerson studies, and ethics in this book of deep existential questioning. Each essay in this atypical, philosophical book employs recurring terms, phrases, and questions that characterize our contemporary age. Setting out from the idea of where we are in an almost literal sense, Lysaker takes readers on an intellectual journey intothematic concerns and commitments of broad interest, such as the nature of self and self-experience, ethical life, poetry and philosophy, and history and race. In the manner of Emerson, Cavell, and Rorty, Lysaker's vibrant writing is certain to have a transformative effect on American philosophy today.